Characterisation and evolution of periglacial landscapes in Northern Siberia during the Late Quaternary : remote sensing and GIS studies - Grosse, Guido (Prof. Dr.) (2005)
About 24 % of the land surface in the northern hemisphere are underlayed by permafrost in various states. Permafrost aggradation occurs under special environmental conditions with overall low annual precipitation rates and very low mean annual temperatures. Because the general permafrost occurrence is mainly driven by large-scale climatic conditions, the distribution of permafrost deposits can be considered as an important climate indicator. The region with the most extensive continuous permafrost is Siberia. In northeast Siberia, the ice- and organic-rich permafrost deposits of the Ice Complex are widely distributed. These deposits consist mostly of silty to fine-grained sandy sediments that were accumulated during the Late Pleistocene in an extensive plain on the then subaerial Laptev Sea shelf. One important precondition for the Ice Complex sedimentation was, that the Laptev Sea shelf was not glaciated during the Late Pleistocene, resulting in a mostly continuous accumulation of permafrost sediments for at least this period. This shelf landscape became inundated and eroded in large parts by the Holocene marine transgression after the Last Glacial Maximum. Remnants of this landscape are preserved only in the present day coastal areas. Because the Ice Complex deposits contain a wide variety of palaeo-environmental proxies, it is an excellent palaeo-climate archive for the Late Quaternary in the region. Furthermore, the ice-rich Ice Complex deposits are sensible to climatic change, i.e. climate warming. Because of the large-scale climatic changes at the transition from the Pleistocene to the Holocene, the Ice Complex was subject to extensive thermokarst processes since the Early Holocene. Permafrost deposits are not only an environmental indicator, but also an important climate factor. Tundra wetlands, which have developed in environments with aggrading permafrost, are considered a net sink for carbon, as organic matter is stored in peat or is syn-sedimentary frozen with permafrost aggradation. Contrary, the ...